Woven places - Ackles, Sharla Fell, author; Lundberg, Thomas R., advisor; Knoll, Diane Sparks, committee member; Orman, Jack L., committee member; Voss, Gary Wayne, committee member (Colorado State University. Libraries, 1989)
To view the abstract, please see the full text of the document.
Keywords: Symbolism in art; Weaving